Report from the 4th Cardiovascular Outcome Trial (CVOT) Summit of the Diabetes & Cardiovascular Disease (D&CVD) EASD Study Group - Schnell, Oliver; Standl, Eberhard; Catrinoiu, Doina; Itzhak, Baruch; Lalic, Nebojsa; Rahelic, Dario; Skrha, Jan; Valensi, Paul; Ceriello, Antonio (Cardiovascular diabetology, 2019)
The 4th Cardiovascular Outcome Trial (CVOT) Summit of the Diabetes & Cardiovascular Disease (D&CVD) EASD Study Group was held in Munich on 25-26 October 2018. As in previous years, this summit served as a reference meeting for in-depth discussions on the topic of recently completed and presented CVOTs. This year, focus was placed on the CVOTs CARMELINA, DECLARE-TIMI 58 and Harmony Outcomes. Trial implications for diabetes management and the impact of the new ADA/EASD consensus statement treatment algorithm were highlighted for diabetologists, cardiologists, endocrinologists, nephrologists and general practitioners. Discussions evolved from CVOTs to additional therapy options for heart failure (ARNI), knowledge gained for adjunct therapy of type 1 diabetes and, on the occasion of the 10 year anniversary of the FDA's "Guidance for Industry: "should CVOTs be continued and/or modified?" The 5th Cardiovascular Outcome Trial Summit will be held in Munich on 24-25 October 2019 ( http://www.cvot.org ).
Keywords: biomedicínský výzkum; mezioborová komunikace; klinické zkoušky jako téma; Clinical Trials as Topic; výsledek terapie; kooperační chování; diabetes mellitus; lidé; Hypoglycemic Agents; endokrinologie; Endocrinology; Treatment Outcome; Cooperative Behavior; hypoglykemika; směrnice pro lékařskou praxi jako téma; Cardiovascular Diseases; Practice Guidelines as Topic; kardiologie; Cardiology; Interdisciplinary Communication; kardiovaskulární nemoci; Diabetes Mellitus; Biomedical Research; Humans